Mekanisme Delta atas Perubahan Status SPT Masa PPN CV. PDM di KKP Zainal Arifin - AULIA ZAHRA KHOIRUNNISA (FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, 2026)
This Final Report aims to determine the Delta mechanism applied in the correction of the Value Added Tax (VAT) Periodic Tax Return at CV. PDM through the Coretax Administration System. This report was prepared based on the implementation of the Coretax Administration System, which applies the Delta Tax Return mechanism by reporting only the differences in data changes without replacing all previously reported data. The report employed a descriptive qualitative approach using observation, interviews, documentation, and literature study as data collection techniques. The results showed that the VAT Periodic Tax Return correction was carried out after a review and reconciliation process indicated that the overpayment position reported in the original VAT Return did not fully reflect the actual VAT position of the tax period because it was still affected by the previous period’s VAT overpayment compensation. After recalculating Output VAT and Input VAT, an additional VAT payable amounting to Rp29.159.096 was identified. The recalculation reduced the VAT overpayment position from Rp1.582.699.441 to Rp1.553.540.345, resulting in a Delta amount of Rp29.159.096 that was treated as an underpayment arising from the VAT Return correction. The correction process included data reconciliation, preparation of working papers, recalculation of the VAT position, data input into the Coretax system, payment of the tax underpayment, and submission of the corrected VAT Return. Based on the findings, the Delta mechanism in the Coretax system supports a more systematic VAT Return correction process by recording and calculating only the differences resulting from data changes. However, careful reconciliation and validation of tax data remain necessary to ensure accurate tax reporting. Keywords: Delta VAT Return, Coretax, VAT Return Correction, VAT Status Change, VAT Underpayment.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: DELTA SPT; PPN